TOWARDS SUSTAINABLE INNOVATION IN LANGUAGE EDUCATION: EXPLORING KEY FACTORS INFLUENCING TEACHER SATISFACTION WITH MAN-MACHINE COLLABORATIVE TEACHING - Xuemei, Wei (Bhandar: Harvesting Community Service in Asia, 2025)
This study investigates the key factors influencing the implementation of man-machine collaborative teaching and explores college English teachers’ satisfaction with this innovative pedagogical model. Drawing on a quantitative approach, data were collected from 250 college English teachers across 12 universities in China. The findings reveal five critical factors shaping the effectiveness of man-machine collaboration: teachers’ artificial intelligence literacy, availability of teaching hardware and software support, preparation of teaching techniques, the presence of an effective incentive and evaluation system, and access to professional training. Among these, professional training was reported as the most satisfactory element, while other aspects—particularly technological infrastructure and institutional support—were rated significantly lower. These disparities highlight challenges in achieving sustainable integration of technology in language education. From the perspective of educational innovation, this research underscores the need for comprehensive, teacher-centered strategies that not only introduce technological tools but also ensure long-term support systems to foster equitable and effective digital transformation in education. The findings contribute to the discourse on sustainable educational models by identifying essential components for successful human-technology symbiosis in teaching practices.